Fabrication of Titanium – Copper Alloy and Study the Antibacterial Activity - Mayada F. Khalil; Sabah A. Salman; Farah T. M. Noori (Academic Science Journal)
The composition of the phases and the microscopic structure of Ti-X% Cu (0, 0.5, 2.5, 5)% prepared alloys was investigated by scanning electron microscope (SEM), and the antibacterial activity was assessed to investigate the effect of the Cu content on the antibacterial activity with or without coating with sliver nanoparticles and graphene nanosheets. The alloys were coated using pulse laser deposition. The alloys of Ti-X%Cu were prepared by the metallurgy process. Finally, the thermal conductivity was studied to determine the effect of increasing the copper content and the coating with nanoparticles. Electron microscopy (SEM) of the alloys before coating showed that the pure titanium is homogeneously distributed and the (Ti-0.5%Cu, Ti-2.5%Cu, and Ti-5%Cu) there are precipitates of (200–800) nm while in scanning electron microscopy (SEM) images of the coated alloys the silver nanoparticles were distributed (20- 26) nm, and graphene oxide was found to be less than (100) nm. The rate of inhibition of bacterial growth increases with increasing concentration copper and with the presence of coatings, and the best inhibition ratio for the sample was (Ti-5%Cu with AgNPs/rGONPs). On the other hand, thermal conductivity of the alloys after coating is less than it was in the uncoated alloys.